COMMUNICATION STRATEGY TO ENCOURAGE EMPLOYEE PARTICIPATION FOR OSH PERFORMANCE IMPROVEMENT AT PT GLOBAL DAIRI ALAMI SUBANG WEST JAWA PROVINCE INDONESIA - Kholil, Kholil; Masjuli, (Archives of Business Research, 2021)
Indonesia with total population reaching 264 million persons is a very potential market share for food products. To meet nutrition needs, PT GLOBAL DAIRI ALAMI was established in 2017 as a milk producer in Indonesia. This company engages in two main activities, i.e. land farming for dairy cow breeding and factory to process the milk with pasteurization and Ultra High Temperature methods before the products are launched to the markets for public consumption via sale representatives. As a new venture, the Company encounters a lot of problems, which include in relation to organization communication in performing Occupational Safety and Health Management System. This Safety and Health Management System is not yet soundly implemented and no communication procedure has been put in place. The objective of this study is to select the most appropriate communication strategy in improving Occupational Safety and Health performance subject to the existing objective conditions using Analytical Hierarchy Process method. Data is collected from discussion with the experts including the owner, board of directors, managers, section heads, and local government officials. The study results show that the owner of company becomes the leading actor in building communication strategies, followed by employees with scores 0.368 and 0.348 respectively. Factor that becomes the first priority for the company is business continuity with budget availability to follow. Occupational Safety and Health training is a priority program necessary to implement Occupational Safety and Health Management System. Based on multi criteria : actor, factor and program, priority strategy necessary to improve OSH performance is to encourage employee participation.